Highly Selective Electrocatalytic CuEDTA Reduction by MoS2 Nanosheets for Efficient Pollutant Removal and Simultaneous Electric Power Output - Qin, Hehe; Liu, Xinru; Liu, Xiangyun; Zhao, Hongying; Mao, Shun (Nano-Micro Letters, 2023)
Electrocatalytic reduction of ethylenediamine tetraacetic acid copper (CuEDTA), a typical refractory heavy metal complexation pollutant, is an environmental benign method that operates at mild condition. Unfortunately, the selective reduction of CuEDTA is still a big challenge in cathodic process. In this work, we report a MoS2 nanosheet/graphite felt (GF) cathode, which achieves an average Faraday efficiency of 29.6% and specific removal rate (SRR) of 0.042 mol/cm2/h for CuEDTA at − 0.65 V vs SCE (saturated calomel electrode), both of which are much higher than those of the commonly reported electrooxidation technology-based removal systems. Moreover, a proof-of-concept CuEDTA/Zn battery with Zn anode and MoS2/GF cathode is demonstrated, which has bifunctions of simultaneous CuEDTA removal and energy output. This is one of the pioneer studies on the electrocatalytic reduction of heavy metal complex and CuEDTA/Zn battery, which brings new insights in developing efficient electrocatalytic reduction system for pollution control and energy output. Highlights: 1 Highly efficient CuEDTA removal by an electrolyzer with MoS2 nanosheet cathode. 2 Higher removal rate and Faraday efficiency compared with other widely reported electrocatalytic technologies. 3 CuEDTA/Zn primary battery is constructed for the first time to realize CuEDTA removal and synchronous power generation.